Some Observations on Growth, Branching Behaviour and Flowering of Teak (Tectona grandis, L.f.) in Relation to Light - Nanda, K. K. (Indian Forester, 1962)
This paper deals with observations on the growth and flowering behaviour of the main shoot and branches of teak (Tectona grandis, L.f.). Trees growing in close stands have very few branches on their lower part and grow quite tall. On the other hand those growing either singly or on the border show profuse branching and rebranching which gives the tree a broad much branched appearance. The flowering of the main shoot as well as branches is terminal. In close stands flowering occurs only in dominant and co-dominant trees and is confined to the upper parts which are exposed to bright sunlight. There are no inflorescences either on the lower parts of these trees or on those which grow under a thick canopy. Flowering is profuse on all sides in trees which are growing singly. As against this in trees growing on the border of thick stands flowering is confined to the lighted side and is more or less completely absent on the shaded side. These differences in growth and flowering are ascribed to the differences in the intensity of light to which these plants are exposed while growing in different situations. It is shown that the curtailment of light delays not only the initiation of flower buds but also their development into flowers as well as in the production and ripening of fruits. The emergence of branches and their flowering appears to be controlled by factors which are related to ageing or completion of the developmental process of the main shoot or the branch on which these are produced. The first branch emerges from the node immediately below the previous year’s inflorescence and the second one from the node next below it and so on. The flowering of these branches also follows the same order. This basipetal sequence in the emergency and flowering is exhibited even by secondary, tertiary, quarternary and further branches. The results are discussed in the light of branching and flowering behaviour of other plants and their practical significance is pointed out.